Validation of a rapid type 1 diabetes autoantibody screening assay for community-based screening of organ donors to identify subjects at increased risk for the disease. (4th May 2016) - Wasserfall, C; Montgomery, E; Yu, L; Michels, A; Gianani, R; Pugliese, A; Nierras, C; Kaddis, J S; Schatz, D A; Bonifacio, E; Atkinson, M A
Summary: The Network for Pancreatic Organ donors with Diabetes (nPOD) programme was developed in response to an unmet research need for human pancreatic tissue obtained from individuals with type 1 diabetes mellitus and people at increased risk [i.e. autoantibody (AAb)-positive] for the disease. This necessitated the establishment of a type 1 diabetes-specific AAb screening platform for organ procurement organizations (OPOs). Assay protocols for commercially available enzyme-linked immunosorbent assays (elisa s) determining AAb against glutamic acid decarboxylase (GADA), insulinoma-associated protein-2 (IA-2A) and zinc transporter-8 (ZnT8A) were modified to identify AAb-positive donors within strict time requirements associated with organ donation programmes. These rapid elisa s were evaluated by the international islet AAb standardization programme (IASP) and used by OPO laboratories as an adjunct to routine serological tests evaluating donors for organ transplantation. The rapid elisa s performed well in three IASPs (2011, 2013, 2015) with 98-100% specificity for all three assays, including sensitivities of 64–82% (GADA), 60–64% (IA-2A) and 62–68% (ZnT8A). Since 2009, nPOD has screened 4442 organ donors by rapid elisa ; 250 (5·6%) were identified as positive for one AAb and 14 (0.3%) for multiple AAb with 20 of these cases received by nPOD for follow-up studies (14 GADA+, two IA-2A +, four multiple AAb-positive). Rapid screening for type 1 diabetes-associated AAb in organ donors is feasible, allowing for identification of non-diabetic, high-risk individuals and procurement of valuable tissues for natural history studies of this disease.